2010
DOI: 10.1159/000320065
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Endoscopic Imaging Methods for Colon Neoplasia

Abstract: The main goal of lumenal endoscopic visualization of the colon is to detect mucosal pathologies, which when removed will result in cure or palliation of a disease process. Whereas traditionally endoscopic imaging was performed with fiber-optic technology, currently there are many new methods that improve our visual acuity when evaluating the colon mucosa. Most of these methods are collectively called ‘advanced colonic imaging’. The 2 main aims of standard (white light) and advanced colonic imaging are to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…DBC uses different dye agents which are divided into absorptive agents (Lugol, methylene blue, toluidine blue, and cresyl violet), contrast agents (indigo carmine, acetic acid) and reactive staining agents (congo red, phenol red). Dye agents are mostly applied via standard spraying or plain biliary ERCP catheters [10]. Various studies have shown the potential of chromoendoscopy to enhance detection of preneoplastic and neoplastic lesions in IBD.…”
Section: Advanced Endoscopic Imaging Methodsmentioning
confidence: 99%
“…DBC uses different dye agents which are divided into absorptive agents (Lugol, methylene blue, toluidine blue, and cresyl violet), contrast agents (indigo carmine, acetic acid) and reactive staining agents (congo red, phenol red). Dye agents are mostly applied via standard spraying or plain biliary ERCP catheters [10]. Various studies have shown the potential of chromoendoscopy to enhance detection of preneoplastic and neoplastic lesions in IBD.…”
Section: Advanced Endoscopic Imaging Methodsmentioning
confidence: 99%
“…Chromoendoscopy in combination with high magnification, allows a better definition of spreading and degree of inflammation, if compared with standard white light colonoscopy, in particular in patient with IBD. In addition, these techniques highly improve early detection of intrae pithelial CRC [20] . A randomized controlled trial has evaluated the chromoendoscopy for early detection of intraepithelial neoplasia and CRC in UC.…”
Section: Chromoendoscopymentioning
confidence: 99%
“…1,2 In an attempt to overcome the limitations of white-light endoscopy, dye-based chromoendoscopy (DBC) techniques were introduced more than one decade ago. 3,4 DBC has been proven to be feasible for improved detection and characterization rates of various GI lesions. In this context, one early study evaluated the efficacy of indigocarmine dye spraying in 52 patients undergoing screening colonoscopy.…”
Section: E Ndoscopic Imaging Of the Gastrointestinal (Gi)mentioning
confidence: 99%
“…However, standard white‐light endoscopy may miss a significant amount of lesions, especially within the colorectum, and may also lead to a misinterpretation of findings, thereby resulting in delayed or suboptimal therapies . In an attempt to overcome the limitations of white‐light endoscopy, dye‐based chromoendoscopy (DBC) techniques were introduced more than one decade ago . DBC has been proven to be feasible for improved detection and characterization rates of various GI lesions.…”
Section: Introductionmentioning
confidence: 99%